2021
DOI: 10.1101/2021.03.01.433110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrapotent miniproteins targeting the receptor-binding domain protect against SARS-CoV-2 infection and disease in mice

Abstract: SUMMARYDespite the introduction of public health measures and spike protein-based vaccines to mitigate the COVID-19 pandemic, SARS-CoV-2 infections and deaths continue to rise. Previously, we used a structural design approach to develop picomolar range miniproteins targeting the SARS-CoV-2 receptor binding domain. Here, we investigated the capacity of modified versions of one lead binder, LCB1, to protect against SARS-CoV-2-mediated lung disease in human ACE2-expressing transgenic mice. Systemic administration… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…A single nasal dose also reduced infection in the lung even when given as many as 5 days before or 2 days after virus inoculation. Importantly, the protein was demonstrated to protect animals against a historical strain (WA1/2020), an emerging B.1.1.7 variant, and a variant encoding key E484K and N501Y spike protein mutations [ 57 ]. These data support development of such antiviral miniproteins for prevention or treatment of COVID-19.…”
Section: Emerging Targets Emerging Modalitiesmentioning
confidence: 99%
“…A single nasal dose also reduced infection in the lung even when given as many as 5 days before or 2 days after virus inoculation. Importantly, the protein was demonstrated to protect animals against a historical strain (WA1/2020), an emerging B.1.1.7 variant, and a variant encoding key E484K and N501Y spike protein mutations [ 57 ]. These data support development of such antiviral miniproteins for prevention or treatment of COVID-19.…”
Section: Emerging Targets Emerging Modalitiesmentioning
confidence: 99%
“…An alternative approach to the problem of short serum half-life is to avoid systemic administration altogether. This has been demonstrated through the generation of small ACE2 derived “miniproteins” which may be administered intranasally allowing access to the lung, a major site of COVID-19 pathogenesis (L. Y. Cao et al, 2020 ; Case et al, 2021 ). Sole use of inhalational therapeutics however will not address the multiorgan tropism of SARS-CoV-2 and the use of truncated ACE2 peptides may allow future mutational escape.…”
mentioning
confidence: 99%
“…With the outbreak of the SARS-CoV-2 coronavirus pandemic we applied our method to design miniproteins targeting the receptor binding domain of the SARS-CoV-2 Spike protein near the ACE2 binding site to block receptor engagement. Due to the pressing need for coronavirus therapeutics, we recently described the results of these efforts 37 ahead of those described in this manuscript; As in the case of FGFR2, IL-7Rα and VirB8, the method yielded picomolar binders, which are among the most potent compounds known to inhibit the virus in cell culture (IC50 0.15ng/ml) and subsequent animal experiments have shown that they provide potent protection against the virus in vivo 38 . The modular nature of the miniprotein binders enables their rapid integration into designed diagnostic biosensors for both influenza and SARS-CoV-2 binders 39 .…”
Section: )mentioning
confidence: 99%